Motivation for Second Language Learning in the Czech Armed Forces - Holcner, Vladan; Dvořák, Jiří; Vápeník, Jiří (2023)
The subject matter of the paper is motivation for second language learning under specific conditions of military service in the Czech Armed Forces. Motivation is the fundamental source of any human action, influencing goals and objectives, attitudes and efforts but also results achieved by each individual. As such, motivation belongs to the most important factors of learners´ success. The paper is based on an explanatory research perspective, aiming at identifying the relative importance of different factors of motivation in second language learning. The presented paper methodology consists of a questionnaire survey, followed by an analysis and interpretation of gathered data. The research material, covered by the survey, is the motivation of the Czech Armed Forces personnel attending foreign language courses to learn second foreign language at the University of Defence Language Centre in 2022. This survey has been designed to enable language educators to identify and further analyse relative significance of individual motivational factors and their perception by second language learners as either internal, or external. As the survey outcomes show, the Czech military personnel motivation to learn second foreign language is not primarily generated by their current job needs and requirements. At the same time, the Czech military personnel attending foreign language courses perceive their learning motivation as predominantly internal.
Keywords: motivation; second language; learning; motivational factor; survey; Czech Armed Forces